Paradigma Komunikasi Pemasaran Terpadu Merumuskan Strategi Branding Starbucks Kintamani Ekologis Kontekstual - Ni Kadek Renita Dwi Handayani; Anak Agung Mia Intentilia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This research seeks to explore the application of the integrated marketing communications paradigm in developing a branding strategy that is both contextually relevant and environmentally sustainable at Starbucks Kintamani. The study employs a descriptive qualitative approach, gathering data through structured interviews with managers, employees, and other relevant stakeholders. visitors, direct field observations, and document studies related to the coffee shop's marketing activities. The research findings show that Starbucks Kintamani consistently integrates various aspects of marketing communications such as advertising, promotions, events, public relations, direct marketing, digital marketing, and direct selling in building a strong brand image. This approach emphasizes the aesthetic values ​​of nature and environmental conservation that are relevant to the local context, thus creating deep emotional attachment and loyalty from consumers. In addition, this branding strategy provides inspiration for local coffee entrepreneurs in developing an authentic and sustainable brand identity. This study enriches theoretical and practical insights in the field of integrated marketing communications and branding strategies based on environmental values ​​and contextual aesthetics.